2011
DOI: 10.3982/ecta8803
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Female Labor Supply

Abstract: The increase in female employment and participation rates is one of the most dramatic changes to have taken place in the economy during the last century. However, while the employment rate of married women more than doubled during the last 50 years, that of unmarried women remained almost constant. To empirically analyze these trends, we estimate a female dynamic labor supply model using an extended version of Eckstein and Wolpin (1989) to compare the various explanations in the literature for the observed tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…One-year additional education attainment is expected to increase the female labor participation rate by about 5.7% for 125 countries. Several studies that found a positive influence of education on women's labor supply are Nam (1991), Eun (2007), Lim (2017), Eckstein andLifshitz (2011), Cameron et al (2001), Abbas (2013), Hafeez andAhmed (2002), andChamlou et al (2011). However, Heath and Jayachandran (2016) argued that increased education did not universally translate into a higher probability of working, as in the case of Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…One-year additional education attainment is expected to increase the female labor participation rate by about 5.7% for 125 countries. Several studies that found a positive influence of education on women's labor supply are Nam (1991), Eun (2007), Lim (2017), Eckstein andLifshitz (2011), Cameron et al (2001), Abbas (2013), Hafeez andAhmed (2002), andChamlou et al (2011). However, Heath and Jayachandran (2016) argued that increased education did not universally translate into a higher probability of working, as in the case of Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done to understand FLFP across the globe, in India, and specifically in Surat city. Eckstein & Lifshitzi (2011) used a dynamic model to understand FLFP and found that education level leads to a 33% increase in female employment and a narrow wage gap leads to a 20% increase in female labour supply. About 40% of the female labour supply remains unexplained due to household characteristics, which can be examined empirically.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Better educated females are more likely to join the labour market since education raises their potential earnings relative to household work (Eckstein and Lifshitz, 2011). Pissarides et al (2005) report that the employment rate of highly educated women in Europe is higher than those with a lower level of education, with the former also exhibiting a smaller gender gap in employment.…”
Section: Brief Literature Reviewmentioning
confidence: 99%